MarketSim : - Ruffer, Rochelle L. (Thomson / South-Western, 2005)
Marketsim consists of two parts: Jeremy's market and Adam' market. In Jeremy's market each student is responsible for a household that consumes and produces goods. You also will be able to trade with the households run by your classmates. Your goal is to try to pick a production and trading strategy that gives your household the highest possible level of happiness. In Adam's market you will be responsible for both a household and a firm, and money is used to make transactions between firms and households.